Fostering sports for healthy community in affordable housing programs - Mat Isa, Norlaili; Daud, Mahyuddin (The Journal of Health and Translational Medicine (JUMMEC), 2021)
The necessary provisions for health include solidity, accommodation, food, wealth with regards to financial and ecological sustainability, and social justice.The provision of an adequate housing is crucial for enhancing a community's quality of life through providing healthy welfare, sufficient employment, financial stability, and safety. While inadequate housing has resulted in numerous health and social issues in the community.To focus on the values, lifestyles and social aspects of the community's everyday lives, the Government launched the National Community Policy. Among the components is sports and recreational activities to be promoted as part of the healthy community lifestyle. As part of wellbeing of the society, the community’s role will look after health and have an educated mind by keeping involved. As such, the aims of this paper are to explore the sports’ role in safeguarding healthy community and to promote sports community integrated as part of the affordable housing programme. Literature and content research on different platforms from previous reports, articles and mass media can provide an overview into the need on sports community policy as sustainable development targets for affordable housing program. The research will be restricted to international and local policy applicable in recognising the right to healthy community. This paper concludes that sports community should be assimilated in affordable housing program in fostering its sustainability.